Neuroscience Techniques in Studying Advertisements Effectiveness: An Experimental Investigation - Agata WAWRZYNIAK; Barbara WASIKOWSKA (Communications of International Proceedings, 2020)
The aim of the article is to familiarise the reader with the procedure of conducting marketing studies with the use neuroscience techniques including electroencephalography (EEG), galvanic skin response (GSR), electrocardiography (ECG), and eye tracking (ET) in order to identify those characteristics which should be present in marketing communication. In the present research we were interested in identification of factors which are taken into consideration when choosing a product on the yoghurt market. The first part of the study was constituted by an experiment with the use of the following techniques: EEG, GSR, and ECG. We recorded signals from a group of 44 healthy subjects while they were watching a documentary intermingled by a series of TV advertisements. The second part of the study was conducted with the use of two methods of gathering empirical data: eye tracking and a questionnaire. The aim of this experiment was to collect data that would enable us to identify which characteristics of yoghurt packaging are significant from the point of view of choices made by the respondents (n = 32). Data analysis shows which commercial was remembered and why. Findings also show what elements of TV advertisement evoke positive and negative emotions. When it comes to eye tracking data, the results obtained have allowed us to establish which elements placed on the yoghurt packages the participants noticed or focused on, and which were entirely ignored. In conclusion, EEG and eye tracking methodologies could be used to obtain information not obtainable with verbal interviews. We argue that the use of these methods by a company may significantly improve the management’s existing knowledge about their clients and facilitate the creation of appropriate strategies in the future, e.g. product launch strategies. Further research with an extended set of subjects will be necessary to further validate the observations reported in this article.
Keywords: electroencephalography (EEG); eye tracking; perception of packaging; marketing communication